The application of ubiquitous multimodal synchronous data capture in CAD. (February 2015) - Sivanathan, Aparajithan; Lim, Theodore; Ritchie, James; Sung, Raymond; Kosmadoudi, Zoe; Liu, Ying
Abstract: Design is an interactive and iterative process where the designer's skills and knowledge are fused with emotive rationales aided by design tools. A design solution is thus influenced by the designer's creativity, experience and emotional perception. Consequently, there is a need within computer aided design (CAD) research for ubiquitous tools to capture the affective states of engineers during design activities to further understand the product design process. This paper proposes a generic framework for ubiquitous multimodal synchronous data capture, based around the capture of CAD system activities, to monitor and log a variety of inputs, interactions, biophysical data and design solutions with a view to providing meta and chronological performance data for post design task analysis. The framework has been employed in two use cases namely, a CAD station activity and a collaborative design review. The results of these trials validated the architecture and use of the ubiquitous data capture approach demonstrating the practical application of time-phased data capture, analysis and the subsequent output of metadata in CAD environments providing a new perspective on, and a new way of investigating CAD-based design activities. This research also extrapolates the framework's usefulness into future CAD and PLM systems by arguing why and how they need to adopt such ubiquitous platforms. It also subjectively points to potential opportunities and issues that might arise when implementing the ubiquitous multimodal metadata architecture in a real-life environment. Highlights: A generic ubiquitous data capture framework is demonstrated via two case studies. Variety of inputs, interactions, biophysical data and design solutions are captured. Tight temporal synchronisation with commodity data logging tools is achieved. Demonstrates engineering knowledge capture linking CAD and PLM via generated metadata. The framework's use in future CAD and PLM systems is extrapolated.